Framingham score, renal dysfunction, and cardiovascular risk in liver transplant patients. Issue 6 (June 2015) - Di Maira, Tommaso; Rubin, Angel; Puchades, Lorena; Aguilera, Victoria; Vinaixa, Carmen; Garcia, Maria; De Maria, Nicola; Villa, Erica; Lopez‐Andujar, Rafael; San Juan, Fernando; Montalva, Eva; Perez, Judith; et al.
Abstract : Cardiovascular (CV) events represent major impediments to the long‐term survival of liver transplantation (LT) patients. The aim of this study was to assess whether the Framingham risk score (FRS) at transplantation can predict the development of post‐LT cardiovascular events (CVEs). Patients transplanted between 2006 and 2008 were included. Baseline features, CV risk factors, and CVEs occurring after LT (ischemic heart disease, stroke, heart failure, de novo arrhythmias, and peripheral arterial disease) were recorded. In total, 250 patients (69.6% men) with a median age of 56 years (range, 18‐68 years) were included. At transplantation, 34.4%, 34.4%, and 33.2% of patients, respectively, had a low, moderate, and high FRS with a median FRS of 14.9 (range, 0.09‐30); 14.4% of LT recipients developed at least 1 CVE at a median of 2.619 years (range, 0.006‐6.945 years). In the univariate analysis, factors associated with the development of CVEs were the continuous FRS at LT ( P  = 0.003), age ( P  = 0.007), creatinine clearance [estimated glomerular filtration rate (eGFR); P  = 0.020], and mycophenolate mofetil use at discharge ( P  = 0.011). In the multivariate analysis, only the eGFR [hazard ratio (HR), 0.98; 95% confidence interval (CI), 0.97‐1.00; P  = 0.009] and FRS (HR, 1.06; 95% CI, 1.02‐1.10; P  = 0.002) remained in the model. Moreover, an association was also found between the FRS and overall survival ( P  = 0.004) with 5‐year survival rates of 82.5%, 77.8%, and 61.4% for the low‐, moderate‐, and high‐risk groups, respectively. Continuous FRS, eGFR, and hepatitis C virus infection were independent risk factors for overall mortality. In our series, the FRS and eGFR at LT were able to predict the development of post‐LT CVEs and poor outcomes. Liver Transpl 21:812‐822, 2015 . © 2015 AASLD.